Rancangan Sistem Informasi Keuangan Studi Kasus: Sekolah Menengah Atas (SMA) Negeri 3 Panyabungan - Nanda Aulia Rifki; Ahmad Zakir; Dedi Irwan (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of information technology encourages each individual to think creatively and innovatively tokeep up with the times. So in the area of school finance, which is very much needed right now. The process ofmaking the design of the school's financial information system aims to simplify the student payment process andprovide well-organized financial recapitulation information. This is an opportunity for the author to build anddesign a web-based online school finance application that is able to simplify the payment process without waitinglong. This application makes it easier for school principals to view financial reports without having to coordinatewith the treasurer first, so research is carried out that aims to find out how to build a financial managementinformation system that is in accordance with the expected system. The method used is Prototype which consistsof communication, rapid design, rapid design modeling, prototype formation, system submission to users andfeedback. The result of this research is the existence of a financial information system for the State High School(SMA) 3 Panyabungan which can make school finances more focused.